Implementasi Good Manufacturing Practices (GMP) Pada Proses Pengalengan Ikan Lemuru (Sardinella longiceps) Dengan Media Saus Tomat Di PT. PHI Banyuwangi - Amiyah, Nur; Mardiyah, Ulfatul (Jambura Fish Processing Journal, 2026)
The fish processing industry plays a crucial role in providing nutritious, safe, and high-quality food for consumers. One of the key efforts to ensure product quality and safety is the implementation of Good Manufacturing Practices (GMP) throughout the production stages. This study aims to examine the implementation of GMP in the canning process of lemuru fish (Sardinella longiceps) with tomato sauce at PT. PT. PHI. The research employed a descriptive method with data collection techniques including observation, interviews, and direct participation in the production process. The results show that GMP implementation at PT. PHI complies with the established standards, as indicated by a hygienic production system, consistent quality control, and well-managed documentation. Although there are several aspects that still require improvement, such as upgrading the toilet door system, the company's commitment to continuous improvement indicates that product quality will be maintained. Through proper GMP implementation, PT. PHI is able to maintain consumer trust by providing safe, hygienic, and high-quality canned fish products.